Assessment of the Feasibility of Using Mobile Application in Stunting prevention in Toddlers: Scoping Review - Lubis, Pahyuri; Mufdlilah, Mufdlilah (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Stunting is a developmental disorder in children caused by malnutrition, susceptibility to infection to disease, and low productivity indicated by a long-term lack of food intake. This scoping review aims to identify the feasibility of mobile applications in preventing stunting in toddlers, through Android-based educational media applications so that stunting in toddlers can be prevented. The structure of writing this scoping review using PRISMA with 5 stages according to Arksey and O'Malley. Article search by 2018- 2023 using several databases including PubMed, Science Direct, and Research Gate. Results of the 666 articles obtained There are 29 potentially relevant articles, ten of which met the inclusion criteria. Presented with three themes viz stunting in toddlers, posyandu during the covid-19 period, and use of mobile applications. The conclusion is there is a relationship significant appropriateness of mobile applications in using mobile application effort prevention stunting. Implications include easier access to nutrition and health information, increased parental awareness on parenting and nutrition, and efficiency in monitoring child growth.